If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 0 = 4x + -2x + y + 6y Combine like terms: 4x + -2x = 2x 0 = 2x + y + 6y Combine like terms: y + 6y = 7y 0 = 2x + 7y Solving 0 = 2x + 7y Solving for variable 'x'. Move all terms containing x to the left, all other terms to the right. Add '-2x' to each side of the equation. 0 + -2x = 2x + -2x + 7y Remove the zero: -2x = 2x + -2x + 7y Combine like terms: 2x + -2x = 0 -2x = 0 + 7y -2x = 7y Divide each side by '-2'. x = -3.5y Simplifying x = -3.5y
| 3x^2+27-30=0 | | 2a-4=132 | | 1x^2-12x+36=0 | | x(x^2)=0 | | x^2+576=10x | | x^2+576=10x^2 | | x+24=10x^2 | | x-x=y | | x-3=y | | 96-5x=7x+54 | | 19x^2+19x+12=0 | | -6w=-8 | | x^2=4x+4+100 | | 4y=256 | | 3y-1=(10y-18)/2 | | (3y-1)/2=(10-18) | | (3y-1)=2(10-18) | | 2(3y-1)=10-18 | | (8x-3)=3(5x+6) | | 3(8x-3)=5x+6 | | 8k-6k+3k= | | x+(x-6)=32 | | 32*2=64 | | ln(x-2)+ln(2x+1)=5 | | b(b-6)=27 | | 3a^2b+2a^2b^2=ab^2+a^2b^2 | | b^2=5b | | 11x+8=129 | | b^2=-30-11b | | (t+3)(t-6)=0 | | a+7= | | 27p+17q+p-7q-5p= |